2000
DOI: 10.1291/hypres.23.459
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Excretions of Albumin and Type IV Collagen in Normotensive and Hypertensive Subjects.

Abstract: Plasma albumin leaks into urine as a result of glomerular hypertension and basement membrane injury, while urinary type IV collagen derives from mesangial matrix and glomerular basement membrane. The purpose of this study was to elucidate the pathophysiological significance of these urinary microproteins as an indicator of cardiovascular organ injuries in hypertension. In health-checkup participants without diabetes, proteinuria, or microhematuria, and who were not being treated for hypertension or any other d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
1
11
0
1
Order By: Relevance
“…1): u-IVc had positive correlation with age, blood pressure, u-Prot, u-β 2 MG, NAG, HbA 1 c and SI, while u-IVc had negative correlation with eGFR and serum albumin. These findings were identical to the past knowledge [17,22], which confirmed that the results were true. Moreover, our large-size study enabled multiple regression analysis to find independent factors for u-IVc.…”
Section: Discussionsupporting
confidence: 91%
“…1): u-IVc had positive correlation with age, blood pressure, u-Prot, u-β 2 MG, NAG, HbA 1 c and SI, while u-IVc had negative correlation with eGFR and serum albumin. These findings were identical to the past knowledge [17,22], which confirmed that the results were true. Moreover, our large-size study enabled multiple regression analysis to find independent factors for u-IVc.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, in recent years it has been reported that the urinary concentrations of type IV collagen increase in diabetic nephropathy patients and in db/db mice (13,14). Because type IV collagen in the urine is considered to be derived from mesangial matrix, glomerular basement membrane, and tubulointerstitial tissue, it is likely that urinary excretion of type IV collagen reflects fibrotic changes in diabetic kidneys (23,25). Therefore, the observed SMP-534-induced inhibition of the increase in urinary type IV collagen excretion may also reflect an inhibitory effect of this compound on deterioration of renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that the overproduction of extracellular matrix proteins underlying glomerulosclerosis in diabetes is associated with the increased excretion of type IV collagen in the urine (14,19). In some cases an increase of urinary type IV collagen excretion precedes an increase of urinary albumin excretion (20).…”
Section: Discussionmentioning
confidence: 99%